Niveles de harina de canavalia (Canavalia ensiformis) en la ración de pollos parrilleros en etapa de acabado y su efecto en el rendimiento productivo en Yurimaguas - Ortiz Navarro, Eveling Estefita (2023)
The present investigation was carried out in the facilities of the shed of Mr. Shankar Ríos Pinedo, district of Yurimaguas, Alto Amazonas province, Loreto region. The general objective was to determine the effect of canavalia (Canavalia ensiformis) flour levels on the productive performance of broiler chickens in the finishing stage. Parameters were evaluated: feed consumption, weight gain, feed conversion, carcass yield, economic merit and taste test in 256 broiler chickens-Cobb line. The Completely Random statistical design was used, with 4 treatments and 4 repetitions with a degree of confidence (P<0.05), these treatments were: T0: 0%, T1: 1%, T2: 2% and T3: 3%, level of canavalia flour respectively. The results: the food consumption was: 163.23 g, 168.92 g, 163.77 g and 162.10 g for the treatments T0, T1, T2 and T3 respectively, with no significant statistical difference in the treatments (P>0.05). Regarding the weight increase, there was no significant statistical difference (P>0.05) in the treatments with respect to the control with values of: T0: 80.09 g.; T1: 83.28 g.; T2: 82.32 g. and T3: 82.27 g. No significant statistical difference was found in feed conversion (P>0.05) and with final values of T0: 2.04; T1: 2.03, T2: 1.99 and T3: 1.97. A 0.78% mortality was recorded in the investigation. Regarding carcass yield, values of: T0: 74.13% were obtained; T1: 75.28%; T2: 74.53% and T3: 74.47. The greatest economic merit was achieved in T1 with S/ 2.67. The best meat preference at the time of tasting was: T1: 62.5% and T2: 37.5%. Concluding that, by including canavalia flour with levels of 1, 2 and 3%, it does not affect the productive performance of broiler chickens in the finishing stage.